State Policy Towards Religious Moderation: A Review of the Strategy for Strengthening Religious Moderation in Indonesia - Fauzan Fauzan (PT. Islamic Research Publiser, 2023)
In the direction of state policy, religious moderation has been contained in the National Medium-Term Development Plan (RPJMN) for 2022-2024. The Ministry of Religion is one of the institutions explicitly given by the state to carry out government affairs in the field of religion, especially in strengthening religious moderation. This paper aims to analyze the indicators in implementing the strategy to strengthen the policy direction of religious moderation in the ministry of religion. The method uses library research based on analysis from various reference sources, both books and online journals. This paper concludes that strategies to strengthen the direction of religious moderation are grouped into four indicators: 1). national commitment; 2). Tolerance; 3) non-violence; 4) acceptance of local culture. This paper also shows that the strategy of strengthening moderation requires the participation of all parties. In this case, social agents, community leaders, and religious leaders are expected to play an active role in a moderate attitude toward religion